"INFORMATION VACCINE" AS A TOOL FOR COUNTERING THREATS TO HUMAN COGNITIVE TO SECURITY (Вісник: Міжнародні відносини, 2025)
Background. In the 21st century, wars are increasingly shifting into the realm of human consciousness, where disinformation acts as an "information virus" that undermines trust, divides societies, and weakens democracy, in particular by discrediting its institutions. Since 2014, Ukraine has become one of the most vulnerable countries to systematic cognitive attacks from Russia. This necessitates the development of preventive strategies, based on principles similar to biological immunization. We call this the concept of an "information vaccine." Accordingly, the purpose of the article is to verify the theoretical foundations of this concept, to examine international experience in countering information threats where this concept serves as a theoretical basis, and to propose an approach to building a multilevel system of human cognitive security in the modern digital world.Methods. The methodological basis consists of interdisciplinary approaches encompassing the analysis of cognitive wars, the study of the transformation of the public sphere as a communicative space, the application of the concept of "soft power," theories of discourse and power, metaphor and hyperreality, as well as the study of ongoing conflicts and their communicative dimensions. To substantiate the preventive approach, the inoculation theory is applied, complemented by modern empirical research on "prebunking." The study employs content analysis of international reports, as well as a comparative analysis of the experiences of various countries – the United States, the European Union, China, and Ukraine – in the study and application of cognitive instruments for the protection of state or, as in the case of the EU, collective interests.Results. The study has shown that the concept of the "information vaccine" has a strong theoretical foundation and is supported by empirical examples. In the United States, the key challenges in this domain have been election interference and the QAnon movement; in the EU – Brexit and the development of mechanisms such as EUvsDisinfo and the Digital Services Act; in China – algorithmic governance and the use of big data. NATO has responded to Russian hybrid influence against member states by creating the StratCom COE in Riga as a multinational center for research and countering cognitive threats. In Ukraine, since 2014 Russia has systematically carried out information campaigns regarding the temporarily occupied Crimea and the Donbas regions, the downing of flight MH17 by Russian proxies, vaccination during the COVID-19 pandemic, and energy security; after 2022, these campaigns have aimed to undermine social stability by spreading doubts about Ukraine's ability to preserve its independence. In response, Ukraine has established the Center for Countering Disinformation under the National Security and Defense Council, launched media literacy programs, and developed cooperation with international partners. The study proposes a multilevel "information vaccine model" that includes individual, educational, technological, local, regional, regulatory–institutional, and international levels, which complement one another.Conclusions. The concept of the "information vaccine" emerges not only as a scientific metaphor but also as a comprehensive strategy of preventive information security. Its key objective is to build the resilience of individuals, society, and the state against cognitive attacks through the combination of education, communications, technological innovation, and international cooperation. The decisive outcome is the achievement of a state of "collective immunity," where destructive messages are unable to cause systemic and devastating consequences. Given its unique experience in countering large-scale information attacks, Ukraine can act as a leader in the development and implementation of a global "information vaccine" strategy.